The dark side of the esophagus - Daniela Martins; Rita Marques; Pedro Costa; João Pinto de Sousa (University of São Paulo, 2021)
Acute esophageal necrosis (AEN), also known as "black esophagus," is an entity characterized by the circumferential black appearance of esophageal mucosa, usually associated with hypoperfusion and gastric outlet obstruction. This entity has a reported prevalence of up to 0.2%, affecting predominantly elderly men with multiple comorbidities. Most cases resolve with conservative treatment with no need of surgical intervention. However, the overall prognosis is poor, with mortality reaching one-third of cases due to the patient's underlying illness. In this article we present three cases of patients with AEN.